(untitled) (Journal of Computational Mathematics, 2018)
This paper proposes a direct search frame-based adaptive Barzilai-Borwein method for unconstrained minimization. The method is based on the framework of frame-based algorithms proposed by Coope and Price, but we use the strategy of ABB method and the rotational minimal positive basis to reduce the computation work at each iteration. Under some mild assumptions, the convergence of this approach will be established. Through five hundred and twenty numerical tests using the CUTEr test problem library, we show that the proposed method is promising.